Effect of Modelling Clay on The Performance of Field-Dependent and Field-Independent Senior School Students in Cell Division - Gabriel Ademakinwa Adeoye; Ganiyu Bello; Isaac Olakanmi Abimbola (Indonesian Journal Of Educational Research and Review, 2022)
Cell division has been identified in literature as a hard-to-learn biology process due to poor instructional strategies and students’ inability to delineate between mitosis and meiosis. Hence, there is need to explore alternative strategy such as modelling clay for the concretization of cell division processes. Therefore, this study, conducted to analyse the effects of modelling clay on the performance of field-dependent and field-independent senior school students in cell division. The study is experimental research. Data was collected using observations, adopted and researchers designed tests. Qualitative and quantitative techniques were used for data analysis. The research subject was modelling clay used by 97 intact class students for learning cell division. The findings revealed that there was no significant difference in the performance of field-dependent and field-independent students. Also, there was no interaction between treatment and students’ cognitive styles. Therefore, it was concluded that modelling clay facilitated students learning of cell division irrespective of cognitive styles. The pedagogical implication is that modelling clay can enhance students’ understanding of the life processes taking place in the cell and by extension other biological processes.